Improving medication adherence with adjuvant aromatase inhibitor in women with breast cancer: Study protocol of a randomised controlled trial to evaluate the effect of short message service (SMS) reminder - He Y. (BioMed Central Ltd., 2019)
10.1186/s12885-018-4660-7